2007
DOI: 10.1177/095632020701800206
|View full text |Cite
|
Sign up to set email alerts
|

Tropolone and its Derivatives as Inhibitors of the Helicase Activity of Hepatitis C Virus Nucleotide Triphosphatase/helicase

Abstract: In this report, we demonstrate the interaction of the non-structural protein 3 (NS3) of hepatitis C virus (HCV) with alkaloide tropolone (2-hydroxy-2,4,6-heptatriene-1-one) and its derivatives. The compounds were biochemically screened separately against the ATPase and helicase activities of HCV NS3. In the investigations presented, alkaloide tropolone and its derivatives significantly inhibited the helicase activity of the viral protein when using a DNA substrate, with 50% inhibitory concentration values with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Several compounds have been identified as RNA helicase of inhibitors of flavi- and other RNA viruses (Borowski et al, 2007; Carta et al, 2006; Frick, 2007; Johansson et al, 2003; Maga et al, 2005; Wu et al, 2006; Xi, 2007). Borowski et al, (2002) reported a WNV helicase inhibitor which also was active in cellular assays (IC 50 = 25–30 μM).…”
Section: Targeting Critical Functions Of Individual Flaviviral Prmentioning
confidence: 99%
“…Several compounds have been identified as RNA helicase of inhibitors of flavi- and other RNA viruses (Borowski et al, 2007; Carta et al, 2006; Frick, 2007; Johansson et al, 2003; Maga et al, 2005; Wu et al, 2006; Xi, 2007). Borowski et al, (2002) reported a WNV helicase inhibitor which also was active in cellular assays (IC 50 = 25–30 μM).…”
Section: Targeting Critical Functions Of Individual Flaviviral Prmentioning
confidence: 99%
“…One of the non-structural proteins is a multifunctional enzyme possessing an N-terminal protease domain and a C-terminal ATPase/helicase domain. The helicase portion of non-structural protein 3 (NS3) is needed for HCV RNA replication (16, 17), but while many potent small molecule inhibitors for this helicase target have been discovered (18-21), none have entered the clinic. Many assays specific for HCV helicase activity have been developed such as those based on ELISA (22), scintillation proximity assays (23), flashplate methods (24), and FRET (25, 26) but they all suffer from the same drawbacks as the aforementioned general helicase assays.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2% of open reading frames in eukaryotes code for helicases or helicaselike proteins. Besides eukaryotes, many viruses also code for helicases [32] that have conserved motifs, and helicases are good targets for developing antiviral compounds [33][34][35][36][37]. Helicases are molecular motor proteins that translocate along nucleic acids and separate double-stranded nucleic acids using the energy generated by nucleoside 5 0 -triphosphate (NTP) hydrolysis.…”
Section: Helicase-dependent Dna Amplificationmentioning
confidence: 99%